Estudo sobre participação em associações de bairros em uma região do distrito de Sacomã: uma análise sob a ótica da psicologia social comunitária - Song, Moses (2010)
This work examines three community leaders who exercise the office of president of neighborhood association in three districts of the region of Ipiranga (SP, Brazil). Through the analysis of the speeches in individual interviews, this study aims to understand whether the type of work they perform favors strengthening and development of the local community. The goal is to bring an historic review of the popular movement of neighborhood, in the classic paradigm of social movement. From this, we will discuss the emergence and development of the theoretical framework of Community Social Psychology and their concepts of power and community empowerment, proposing a democratic leadership that promotes the participation of community members. We conclude that these leaders do not encourage community participation, because of internal contradictions in the dynamics of the associations which they manage and because they perform an intermediary role between the State interests and the community. Thus, this movement is characterized as non-politicized, clientelistic and paternalistic